Tailoring electrochemical CO2 reduction via substrate-induced gas diffusion. Issue 13 (10th March 2023) - Chae, Younghyun; Kim, Kyeongsu; Yun, Hyewon; Kim, Dongjin; Jung, Wonsang; Hwang, Yun Jeong; Lee, Ung; Lee, Dong Ki; Min, Byoung Koun; Choi, Woong; Won, Da Hye
Abstract : To design active and selective catalysts for deriving value-added C2+ chemicals from the electrochemical CO2 reduction reaction, comprehensive studies on the catalyst system are necessary. Abstract : To design active and selective catalysts for deriving value-added C2+ chemicals from the electrochemical CO2 reduction reaction (CO2 RR), comprehensive studies on the catalyst system are necessary. However, the substrate-induced properties and their effects have been overlooked despite the importance of extrinsic properties in the CO2 RR. In this study, we investigated the substrate effects on CO2 RR performance by applying well-defined Cu2 O nanocube catalysts to two representative substrates, porous carbon paper, and glassy carbon substrate. Although the same Cu2 O catalyst was applied to both substrates, the product selectivity and total current density varied significantly depending on the type of substrate, especially for the CO Faradaic efficiency (FE). Computational fluid dynamics (CFD) simulation and gas diffusion control experiments revealed that a substrate with porous media ( i.e., carbon paper) can provide an unnoticed gas diffusion pathway of reactant CO2 and the intermediate product, CO. This substrate facilitated CO2 supply to the catalyst layer while letting CO diffuse back from the catalyst layer to the porous media of the substrate, contributing to the high FECO on porous carbon paper. Based on these findings, we rationally developed a double-layered tandem catalyst by employing a different gas diffusion rate and direction, and achieved an exceptionally high FEC2+ of 62.1% on a carbon paper/Cu/Ag-configured catalyst. This study elucidates that the substrate should be carefully considered for designing an efficient CO2 RR system and to avoid the misinterpretation of results. Therefore, gas diffusion, which is the most important extrinsic property relevant to the CO2 RR, is practically influenced by the substrate properties.